The role of emotionality in the acquisition of new concrete and abstract words - Ferré, Pilar; Ventura, David; Comesaña, Montserrat; Fraga, Isabel (Frontiers in Psychology, 2015)
A processing advantage for emotional words relative to neutral words has been widely demonstrated in the monolingual domain (e.g., Kuperman, Estes, Brysbaert, & Warriner, 2014). It is also well known that, in bilingual speakers who have a certain degree of proficiency in their second language, the effects of the affective content of words on cognition are not restricted to the native language (e.g., Ferré, García, Fraga, Sánchez-Casas, & Molero, 2010). The aim of the present study was to test whether this facilitative effect can also be obtained during the very early stages of word acquisition. In the context of a novel word learning paradigm, participants were trained on a set of Basque words by associating them to their Spanish translations. Words’ concreteness and affective valence were orthogonally manipulated. Immediately after the learning phase and one week later, participants were tested in a Basque go-no go lexical decision task as well as in a translation task in which they had to provide the Spanish translation of the Basque words. A similar pattern of results was found across tasks and sessions, revealing main effects of concreteness and emotional content as well as an interaction between both factors. Thus, the emotional content facilitated the acquisition of abstract, but not concrete words, in the new language, with a more reliable effect for negative words than for positive ones. The results are discussed in light of the embodied theoretical view of semantic representation proposed by Kousta,Vigliocco, Vinson, Andrews, and Del Campo (2011).